The effects of low-dose sorafenib on epithelial-mesenchymal transition and multidrug resistance markers in HepG2 cell line - Dönmez Çakıl, Yaprak; Akbulut, Zeynep; Demirel, Gamze; Gülhan, Ranan; Ozunal, Zeynep (The European Research Journal, 2023)
Objectives: Sorafenib is an orally administered tyrosine kinase inhibitor in hepatocellular cancer. Low sorafenib concentrations are attained during pharmacotherapy due to pharmacokinetic profile and patient inadherence. Resistance to treatment is a limitation to improving survival. Underlying mechanisms include epithelial-mesenchymal transition. The aim of the study was to evaluate epithelial-mesenchymal transition and multidrug resistance-related parameters in HepG2 cells following low-dose and short-term sorafenib treatment. Methods: Epithelial-mesenchymal transition and multidrug resistance-related markers were examined by quantitative PCR, flow cytometry, and confocal laser scanning microscopy. Results: An increase in epithelial marker E-cadherin and downregulation of mesenchymal markers Vimentin and Snail1 were detected by gene expression analysis. While P-glycoprotein expression increased, multidrug resistance protein 1, and breast cancer resistance protein mRNA levels did not alter after sorafenib treatment. The accumulation of the ABC transporter substrate rhodamine 123 in the cells increased following the treatment, corresponding to a less efficient efflux of rhodamine 123 and a possible effect on other transporters and mechanisms. Conclusions: The results indicate a protective effect of sorafenib against epithelial-mesenchymal transition and upregulation in P-glycoprotein expression, which is, however, not sufficient to cause less intracellular rhodamine 123 accumulation. The effects of low-dose and short-term sorafenib on epithelial-mesenchymal transition and multidrug resistance-related markers might contribute to enlightening new treatment strategies in hepatocellular cancer.